(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: Analysis of Factors Associated with Hypertension Among Elderly Khmer People in Chau Thanh District, Tra Vinh Province, in 2024. Method: A cross-sectional analytical study was conducted on 400 elderly individuals of Khmer ethnicity. A structured questionnaire was developed in alignment with the study objectives. Results: Some factors associated with the prevalence of hypertension among elderly Khmer people in Chau Thanh district include: age (OR = 3.26; 95% CI: 2.04–5.24; p < 0.001), health insurance (OR = 2.96; 95% CI: 1.01–9.80; p < 0.05), central obesity (OR = 2.28; 95% CI: 1.46–3.56; p < 0.001), habit of consuming salty foods (OR = 23.2; 95% CI: 13.28–40.82; p < 0.001), habit of eating fatty foods (OR = 5.24; 95% CI: 3.08–9.13; p < 0.001), alcohol abuse (OR = 1.85; 95% CI: 1.67–2.06; p < 0.001), current smoking (OR = 5.23; 95% CI: 2.71–10.09; p < 0.001), and insufficient physical activity according to recommendations (OR = 0.31; 95% CI: 0.18–0.54; p < 0.001). Conclusion: The prevalence of hypertension among elderly Khmer individuals in Chau Thanh district is associated with various modifiable and non-modifiable factors. Further studies in other localities are needed to better clarify the extent of these associations in the elderly Khmer population